The use of force against non-state actors: all over the map. (3rd July 2021) - Haque, Adil Ahmad
ABSTRACT : This short article considers the informal 'Arria formula' meeting of the United Nations Security Council convened by Mexico in February 2021. It offers a compressed analysis of many of the statements made during that meeting regarding the substantive issue of inter-state force against non-state actors, identifies important areas of disagreement, and concludes with some observations on the current state of the law and the path forward.